Differences in phototherapy among skin diseases and genders in real‐life conditions—A retrospective analysis of the cumulative doses, numbers of sessions, side effects and costs in 561 patients. Issue 5 (16th April 2021) - Merkel, Tamara Alessia; Navarini, Alexander; Mueller, Simon
Abstract: Background: Phototherapy has been a mainstay therapy for dermatological diseases since more than a century. Although phototherapy is still extensively used and some recommendations exist, only scarce data are available addressing disease‐specific differences in cumulative doses, treatment durations and costs. Knowledge of such differences could help to avoid over‐/undertreatment, predict treatment duration and costs. Therefore, we sought to determine differences in cumulative doses, numbers of sessions, side effects and costs among different skin diseases and genders in real‐life conditions. Methods: In this single‐centre, retrospective study, patients treated with phototherapy between March 2014 and April 2019 were classified into seven diagnostic groups and analysed according to the study goals. Results: Out of 561 patients (age 53.9 ± 20.3 yrs; 52.9% females), 83.7% percent were treated with cabin NB‐UVB (mean cumulative dose 17.79 ± 17.11 J/cm 2 ). Patients with vitiligo and psoriasis were treated with significantly higher cumulative NB‐UVB doses (cabin, local) in comparison with the five other diagnostic groups as were males in comparison with females. Consequently, significantly higher UV‐related costs resulted in patients with vitiligo, psoriasis and males. Patients with atopic dermatitis and pruritus were treated with significantly higher cumulative UVA1 doses compared to patients with non‐atopic eczema. The complication rate (pooled from all UV modalities) in our population was 3.8% (erythema 3.4%, aggravated itch 0.4% and worsening of symptoms 0.2%). Conclusions: Our results demonstrate that cumulative doses and phototherapy‐related costs vary strongly among skin diseases–a fact not adequately considered in recommendations. A more disease‐specific stratification of phototherapy could not only help to optimize outcomes, but also to facilitate comparability of clinical trials using phototherapy.